There is actually 2 ways to solve this, I will show you both.
The first is obvious, solve for x in the first one, and plug it into the 2nd one and get the answer
4x + 7 = 12
4x = 5
x =
![(5)/(4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zikqpj6w0jr30jv60eocrgogzdkyelaujh.png)
8(
) + 3
2 * 5 + 3
10 + 3
13
The 2nd option is to manipulate the 4x + 7 to be 8x + 3
4x + 7 = 12
start by moving the 7 over
4x = 5
multiply both sides by 2
8x = 10
and add 3 to both sides
8x + 3 = 13